Short-term immediate post-shock pacing in adult advanced life support – a feasibility study of modified ALS algorithm. (25th November 2020) - Telec, W; Klosiewicz, T; Zalewski, R; Zukowska, J; Baszko, A; Puslecki, M
Abstract: Introduction: It is well known that the majority of patients remains transiently pulseless after successfull defibrillation shock during routine advanced cardiovascular life support (ACLS). The post-shock asystole is longer than 120 seconds in as many as 25% of patients. Not only asystole, but also profound postshock bradycardia and high degree AV blocks are described as common. The need for post-shock pacing (PSP) in adult ACLS is unknown, but there is extensive use of that feature in implantable cardioverters – defibrillators (ICD). PSP feature is widely used in these devices. The wide utilisation of PSP in ICD patients warrants the research towards any possible benefit of it during ACLS measures. Material and methods: We performed high-fidelity simulation study including 60 paramedic at 20 scenarios. The participants were asked to perform routine resuscitation scenarios according to the AHA ACLS algorithm. In the control group paramedics had to resume compressions after each shock. In experimental group simultaneously with the compressions, transcutaneous pacing with 200 mA output and rate of 80 ppm was delivered. Several parameters were monitored: chest compression fraction, compressions depth and rate, percent of recoiled compression, compressions on correct depth, and other. Results: There were no statistically significant differences between both groups in respect of compressions depth and rate, time needed to achieve advanced airway, initiate and achieve intravenous line, administer medications (Table 1). The detailed results are presented in Table 1. Discussion: According to the best of the authors knowledge, this is the first study describing the feasibility of PSP in resuscitation. The quality of resuscitation depends on adherence to the protocol. Any additional element in the protocol can negatively affect the outcome. In the presented study we present that major ACLS steps are delivered without significant delay when PSP is utilised. Conclusions: The implementation of PSP had no negative impact on adherence to ACLS protocol. The authors see the need for further intensive research in this area. Funding Acknowledgement: Type of funding source: None